Biologically active natural products : microbial technologies and phyto-pharmaceuticals in drug development - Mahapatra, Debarshi Kar; Talele, Swati Gokul; Volova, Tatiana G.; Haghi, A. K. (Palm Bay, FL, USA ; Burlington, ON, Canada : Apple Academic Press ; Boca Raton, FL, USA ; Abingdon, Oxon, UK, 2021)
"Biologically active natural products and their substructures have long been valuable starting points for medicinal chemistry and drug discovery. This new volume explores biologically active natural products and their use in microbial technologies and as phyto-pharmaceuticals in drug development. It presents detailed scientific principles and recent research on applications of nanotechnology in diagnostics and drug delivery. Topics include pharmacotherapeutically active proteins and peptides; the biotechnological potential of hydrogen-oxidizing bacteria; synthesis and production; synthetic colorants, pigments, dyes, and lakes; and more. The use of various plants is discussed in several chapters, including Artemisia, Asteraceae, Abutilon indicum, Prosopis juliflora, Acacia arabica, Aloe barbadensis, Tabermontana divaricate Linn., among others. Key features: Presents key factors of biologically active natural products with their industrial applications, covers basic issues relative to natural pharmaceuticals, provides real-world examples of important issues, provides an understanding of current pathways for professional development in sustainable technology. With the information presented in Biologically Active Natural Products: Microbial Technologies and Phyto-Pharmaceuticals in Drug Development, scientists, faculty, and graduate students will gain a unique insight into nanotechnology and natural pharmaceuticals today with practical implementation in various industrial sectors."--
Azadirachta indica: Imperative Mini-Opinions on an Ethnopharmacological Savior / Anshda Bhatnagar and Debarshi Kar Mahapatra -- Arsenals of Pharmacotherapeutically Active Proteins and Peptides: Old Wine in a New Bottle / Kirti Dubli -- Biotechnological Potential of Hydrogen-Oxidizing Bacteria / Tatiana Gr. Volova, Evgeniy G. Kiselev, and Ekaterina I. Shishatskaya -- Abutilon indicum, Prosopis juliflora, and Acacia arabica as Antibacterial Agents Against Xanthomonas axonopodis pv. punicae / Aishwarya A. Andhare and Ravindra S. Shinde -- Microbial Biotechnology: Synthesis, Production, Challenges, and Opportunities / Akshada A. Bakliwal, Swapnali A. Patil, Meghawati R. Badwar, and Swati G. Talele -- Pharmaceutical Natural and Synthetic Colorants, Pigments, Dyes, and Lakes: Applications, Perspectives, and Regulatory Aspects / Debarshi Kar Mahapatra and Sanjay Kumar Bharti -- Microbial Pigments: A Green Microbial Technology / Eknath Ahire, Swati G. Talele, and Gokul S. Talele -- Ethnopharmacological Perspectives of the Traditional Herb Tabermontana divaricate Linn / Seema Wakodkar, Debarshi Kar Mahapatra, Shilpa Borkar, and Shailaja Latkar -- A Closer View on Various Reported Therapeutically Active Formulations Containing Aloe vera (Aloe barbadensis) / Vaibhav Shende and Debarshi Kar Mahapatra -- Sesquiterpenes in Artemisia and Development of Drugs from Asteraceae / Francisco Torrens and Gloria Castellano.
OCLC-licensed vendor bibliographic record.
Keywords: Drug development; Natural products; Biological products; Microbial biotechnology; Materia medica, Vegetable; Nanotechnology; MEDICAL / Biotechnology; MEDICAL / Pharmacology